Creative Thinking Physics: A Review and Bibliometric Analysis - Dea Arsi Prabaningtias; Edi Istiyono; Diah Mahmuda; Daly Arman; Fitria Arifiyanti (STKIP Singkawang, 2022)
Creative thinking is one of the tallents required for the Industrial Revolution 4.0. The goal of this research is to conduct a comprehensive evaluation of the bibliometric literature on physics students' creative thinking abilities. Scopus data base articles discovered using publish software or perish (pop). This research analyzes 70 of 102 publications discovered in the Scopus database between 1960 to 2020. Mendeley's Reference Manager software is then used to handle the selected reference. After maintaining the database, this study uses Vosviewer software to classify and visualize it. In general, this study serves as an excellent starting point for future research on